Emotions, Emotion Management and Emotional Intelligence in the Workplace: Healthcare Professionals' Experience in Emotionally-Charged Situations - Carminati, Lara (Frontiers in Sociology, 2021)
This perspective article is grounded in a cognitive and context-dependent view on emotions. By considering emotions as socially embedded and constructed, the different but related concepts of Emotion Management and Emotional Intelligence can be introduced. Yet, research juxtaposing and applying them within the healthcare sector to explain healthcare professionals’ multifaceted emotional experiences at work is still scarce. Hence, this article contributes to the literature on emotions by offering an overarching perspective on how the juxtaposition of Emotion Management and Emotional Intelligence may help healthcare professionals to bridge the developmental transition between these two crucial abilities which, in turn, can help them overcome emotional difficulties in complex situations. Such integration would positively influence individuals’ behavioral and mental health, as well as the overall quality of the healthcare system.